Congenital pseudodiphallia -A rare case presentation - Amit Kumar Mishra; Vijay Anand; Ravi Kale (Wolters Kluwer Medknow Publications, 2023)
Diphallia (penile duplication) is a rare congenital malformation with an incidence of about 1 per 5-6 million newborns. The severity of diphallia varies from a small accessory penile-like tissue to complete true penile duplication with other deformities, usually involving the urogenital, gastrointestinal, and musculoskeletal systems. Pseudodiphallia, as a rare kind of diphallia, is characterized by a small accessory penile-like tissue without a normal penile anatomy structure. A 5.5-year-old male child was brought to the pediatric surgery outpatient department by the parents with complaint of difficulty in retracting the prepucial foreskin and the presence of some growth near the glans. There were no other complaints in specific. Clinical examination revealed foreskin retractable with difficulty and small conical lump smaller than the original glans approximately size ~1 cm diameter at the base attached horizontally at the left side of the original glans at the coronal sulcus and visible incomplete clefting in between the 2 glans visible from the aerial view. After approval from anesthetist, the patient was operated under general anesthesia by excision of pseudodiphallia. Urethral catheterization and circumcision of the penis after taking informed parental consent. Postoperatively, the period was uneventful. The patient responded well to the symptomatic treatment and was orally allowed on the same day evening. Urinary catheter was removed on 5th postoperative day. The patient was discharged on oral symptomatic medication and was advice for follow-up.